Ferroelectric and dielectric properties of vanadium-doped Ba(Ti0.90Zr0.10)O-3 ceramics - Moura, F. [UNESP]; Simões, Alexandre Zirpoli [UNESP]; Cavalcante, L. S.; Zaghete, M. A. [UNESP]; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V. Sa, 2008)
Ba(Zr0.10Ti0.90)O-3 (BZT) and V substituted BZT ceramics (BZT:V) were prepared by mixed oxide method and polymeric precursor method. The effect of V5+ addition in the BZT lattice was evaluated by X-ray diffraction (XRD) and Fourier transform Raman (FT-Raman) spectroscopy. When vanadium is introduced in the BZT lattice there is a decrease in the grain size. Substitution of vanadium on B-site broads the dielectric permittivity curve. That can be caused by repulsion of vanadium with their next nearest neighbors leading to a structure which is tetragonally distorted. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Ferroelectrics; Solid-state reactions; Chemical synthesis; Vacancy information